Is Palladium a safe haven asset? - Água, João Pedro Rodrigues Freire Borda d´ (2020)
This dissertation investigates the role of Palladium in the global financial system as a safe haven asset against stocks of major emerging and developed countries. Since the beginning of the 21st century, the price of Palladium has increased steadily and dramatically. Using a daily, weekly and monthly data covering the period of 1978 to 2019, this dissertation finds evidence that Palladium is neither a hedge nor a safe haven asset for major European stock markets, BRIC countries, Australia, Canada and Japan. Nevertheless, we find that Palladium is a safe haven asset in the case of adverse market stocks for US stock market using monthly data. Moreover, we look at particular crisis periods and we notice that Palladium is a safe haven asset for Brazil and US stocks during the Asian crisis in 1997, but in the most recent crisis, it shows a positive co-movement with stocks providing a weak safe haven asset during these periods